Receptor status of tumor as prognostic factor in patients with bilateral breast cancer - Tsyhyka, D.Y.; Hotko, Y.S.; Devinyak, O.T. (Experimental Oncology, 2013)
Aim: To determine the receptor status of tumors as prognostic factor in development of bilateral breast cancer (BBC) and factor of prognosis of disease. Patients and Methods: 272 cases of BBC during the period from 1995 to 2011 in different oncological institutions of Ukraine have been analyzed. Results: Patients with metachronous BBC with positive status of hormone receptors (HR) of tumors have significantly better indices of overall and progression-free survival (three-years — 95%, five-years — 72%), than patients with HR-negative status (among them nobody has survived over 5 years). In patients with synchronous BBC, the receptor status of tumors has similar influence on the prognosis of survival. Nevertheless, indices of overall survival (65%) and progression-free survival (66%) in HR-positive patients were lower than that at metachronous BBC (overall survival and progression-free survival — 72%). Conclusions: Synchronous breast cancer has more aggressive clinical course than metachronous one. It was determined significant influence of receptor status of tumors on the overall survival and progression-free survival in patients with BBC.